2013
DOI: 10.1007/s10600-013-0799-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of the Root Barks of Eucommia ulmoides

Abstract: Eucommia ulmoides Oliv. ("Du Zhong" in Chinese and "Tu Chung" in Korean), the sole species in the genus Eucommia and family Eucommiaceae, is a deciduous tree indigenous in China and widely cultured in eastern Asian countries [1]. The species is highly valued and commonly used in traditional medicines to treat various diseases, especially to relieve hypertension, protect the nervous system, treat diabetics, cure lower back pain, and prevent miscarriage [2,3]. Previous phytochemical investigations of E. ulmoides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that ethyl acetate extract of E. ulmoides flowers had good antibacterial activities against Staphylococcus aureus , Bacillus anthracis , Bacillus subtilis , and Escherichia coli [ 14 ]. The effective components of E. ulmoides include phenolics, flavonoids (such as quercetin and rutin), iridoids (such as geniposide, aucubin, and geniposidic acid), phenylpropanoids (such as chlorogenic acid), lignans (pinoresinol diglucoside), sterols, terpenoids, and polysaccharides [ 15 , 16 ]. Flavonoids are strong antioxidants that can inhibit carcinogenesis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ethyl acetate extract of E. ulmoides flowers had good antibacterial activities against Staphylococcus aureus , Bacillus anthracis , Bacillus subtilis , and Escherichia coli [ 14 ]. The effective components of E. ulmoides include phenolics, flavonoids (such as quercetin and rutin), iridoids (such as geniposide, aucubin, and geniposidic acid), phenylpropanoids (such as chlorogenic acid), lignans (pinoresinol diglucoside), sterols, terpenoids, and polysaccharides [ 15 , 16 ]. Flavonoids are strong antioxidants that can inhibit carcinogenesis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eucommia ulmoides (E. ulmoides), a well-known medicinal plant in China, is abundant in bioactive constituents. Recent studies have demonstrated that E. ulmoides contains many phytochemicals, such as polyphenolics, phenylpropanoids, flavonoids and triterpenes [21][22][23]. Its ready-made products, such as E. ulmoides bark tea, capsules, extract and powder, are widely used for nourishing liver and kidney, strengthening muscles and bones, lowering high blood pressure, miscarriage prevention and so on [24].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption peak of the E. ulmoides extract was observed at 252 and 300 nm which origins from the unsaturated and aromatic compounds. It has been reported that the E. ulmoides bark contain various organic compounds such as polyphenolics, flavonoids, and triterpenes [14][15][16]. The water soluble compounds present in the aqueous extract were found to be responsible for efficient stabilization of nanoparticles and reduction of metal ions.…”
Section: Controllable Synthesis Of Aunpsmentioning
confidence: 99%
“…Recent studies have demonstrated that E. ulmoides contains many phytochemicals such as polyphenolics, phenylpropanoids, flavonoids, and triterpenes [14][15][16]. Its ready-made products, such as E. ulmoides bark tea, capsules, extract, and powder, are widely used for nourishing liver and kidney, strengthening muscles and bones, lowering high blood pressure, miscarriage prevention, and so on [17].…”
Section: Introductionmentioning
confidence: 99%